2017
DOI: 10.1097/pas.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Somatic PDGFRB Mutations in Sporadic Infantile/Solitary Adult Myofibromas But Not in Angioleiomyomas and Myopericytomas

Abstract: Infantile myofibroma (MF) is an uncommon benign myofibroblastic tumor of infancy and childhood. Solitary adult MF shares similar features with infantile MF. The lesions occur in 3 clinicopathologic settings: solitary, multicentric, and generalized and can be either sporadic or familial. Traditionally, infantile MF has been included in the spectrum of infantile hemangiopericytoma. The recent World Health Organization classification listed MF, angioleiomyoma, and myopericytoma under the general heading of periva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 26 publications
5
68
2
Order By: Relevance
“…Additionally a recent study has demonstrated that in fact >70% of both classic adult and infantile myofibromas are associated with distinct genetic abnormalities, i.e. PDGFRB mutations, different from our cohort of cases 9 . Moreover, our previous studies have shown that recurrent NOTCH gene rearrangements were only identified in glomus tumors, while the other pericytic/ perivascular tumors do not.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally a recent study has demonstrated that in fact >70% of both classic adult and infantile myofibromas are associated with distinct genetic abnormalities, i.e. PDGFRB mutations, different from our cohort of cases 9 . Moreover, our previous studies have shown that recurrent NOTCH gene rearrangements were only identified in glomus tumors, while the other pericytic/ perivascular tumors do not.…”
Section: Discussioncontrasting
confidence: 82%
“…We are aware that in cases with very low variant allele frequency (VAF) the mutations could have been missed. However, other groups were able to successfully detect somatic mutations in a high proportion of sporadic myofibroma cases using Sanger sequencing only . Therefore, if PDGFRB mutations were highly frequent in odontogenic myxoma, we should have been able to detect mutations at least in a few cases.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that, different from myofibromas, odontogenic myxomas do not harbor PDGFRB exon 12 and 14 mutations. Agaimy et al reported PDGFRB somatic mutations as molecular driver events in the majority of sporadic infantile and adult solitary myofibromas (75% and 69%, respectively). These genetic alterations were detected not only in the soft tissue tumors, but also in the intra‐osseous lesions (Table ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations